Microsphere as a Novel Drug Delivery System: A Review - Namdev, Abhisek; Issarani, Roshan; Khinchi, M. P (Asian Journal of Pharmaceutical Research and Development, 2015)
The modified release product encompass the dosage form design includes enteric coated tablets (including immediaterelease), and extended-release products where drug release is controlled by the dosage form to occur over a period of hours. Concept of targeted delivery is designed for attempting to concentrate the drug in the tissue and reducing the concentration in the remaining tissue of the body. By using the polymer by coupling the drug in the carrier such as microspheres, nanoparticles, liposomes, niosomes, pharmacosomes, aquasomes etc. which modulate the release and absorption characteristics of the drug. Microspheres are characteristically free flowing powders consist of drug and polymers having a particle size ranging from 1-1000 μm. In future by using various technology and strategies in microsphere that find the central place in novel drug delivery.